A Broadband High Gain, Noise-Canceling Balun LNA with 3–5 GHz UWB Receivers for Medical Applications - A. Kareem, Thaar; Trabelsi, Hatem (International Journal of Online and Biomedical Engineering (iJOE), 2022)
The Ultra-Wideband Wireless Body Area Network (UWB-WBAN) has been identified to provide an efficient, low-power, and improved wireless communication between sensor nodes worn by the human body to monitor physiological signals. The first part of the UWB receiver is a low noise amplifier (LNA). This article describes an upgrade to a sort of balun LNA that is entirely transistor-based and devoid of inductors for medical worn communication service. The balun LNA uses common gate and a common source configuration which cancels the noise generated by the common gate. This work uses the transistors in place of resistors to minimize the integrated circuit's area, as well as finding the best values for the dimensions of the transistor to minimize energy consumption, achieve a high gain and good linearity. This reduces the noise figure. The designed system utilizes the UWB frequency range of 3-5 GHz and a voltage supply of 1.8V. The designed balun LNA is able to achieve a peak gain of 25.5 dB and noise figure (NF) less than 3.2-3.5 dB using 180µm TSMC CMOS technology. The IIP3 is quite high at 2 dBm, whereas the IIP2 maximum is 21 dBm. The entire power consumption is less than 7.2 mW.